Comparison of macular parameters after femtosecond laser–assisted and conventional cataract surgery in age‐related macular degeneration. Issue 1 (January 2018) - Enz, Tim J.; Faes, Livia; Bachmann, Lucas M.; Thiel, Michael A.; Howell, Jeremy P.; Boehni, Sophie C.; Bittner, Mario; Schmid, Martin K.
Abstract : Purpose : To evaluate differences in postoperative central macular thickness, central macular volume, corrected distance visual acuity (CDVA), and number of intravitreal anti‐vascular endothelial growth factor (VEGF) injections between conventional and femtosecond laser–assisted cataract surgery in wet age‐related macular degeneration (AMD). Setting : Tertiary referral center, Lucerne, Switzerland. Design : Retrospective case series. Methods : Consecutive patients with AMD and cataract were enrolled between January 2010 and December 2015. Associations between postoperative changes in central macular thickness, central macular volume, CDVA, and number of anti‐VEGF injections with type of surgery were assessed statistically. Results : The study comprised 140 eyes (110 patients). No differences in postoperative central macular thickness (−9.20 μm; 95% confidence interval [CI], −41.68 to 23.28; P = .576), central macular volume (−0.08 mm 2 ; 95% CI, −0.36 to 0.19; P = .553), visual acuity (0.03 logarithm of the minimum angle of resolution; 95% CI, −0.09 to 0.15; P = .647) or postoperative number of anti‐VEGF injections (0.30; 95% CI, −0.45 to 1.05; P = .427) were found between the femtosecond laser group and the conventional group over a mean follow‐up of 619 days ± 473 (SD). In the 33 eyes that had optical coherence tomography measurement within a postoperative period of 2 weeks, the central macular volume was significantly lower in femtosecond laser–treated eyes (−0.71 mm 2 ; 95% CI, −1.19 to −0.23; P = .005). Conclusions : Overall, the postoperative course between wet AMD after femtosecond laser and conventional cataract surgery was equal. During the early follow‐up, femtosecond laser–treated eyes had less subclinical macular edema, indicating a possible benefit for patients with macular vulnerability.